Perilaku impulse buying terhadap layanan spaylater dan gratis ongkir sebagai strategi marketing shopee - Dewi Kartika Sandra; Cindi Audia Fithrotunisa (Jurnal Riset Pendidikan Ekonomi, 2023)
The development of the digital world in the 4.0 era has made many online buying and selling platforms progress which makes it easier for users to make transactions. People who previously only made transactions offline, are now spoiled for choice with the convenience of shopping online. In line with that, now more and more consumers tend to buy goods excessively without thinking. This condition is better known as impulse buying. This study aims to analyze Impulse Buying behavior towards Spaylater services. This study uses a qualitative method. In this study the data used is secondary data. Data collection uses library research by searching for and reading journals and theories relevant to research and conducting searches on various popular official sites. Data is presented with a descriptive approach. The results of the study stated that Spaylater and Free Shipping can lead to impulse buying behavior among various online media users, Shopee. There are four forms of impulsivity that arise, pure impulse buying, reminder impulse buying, planned impulse buying and suggestion impulse buying. At certain limits, impulse buying behavior is good, but consumerism is certainly no longer good. Therefore, consumers are advised to be wise in buying, while businesses are advised to provide advertisements with adequate education. Not only limited to chasing big sales targets.